Alpha-cluster preformation probability in even-even actinide nuclei - Alsaif, Norah A.M.; Ahmed, Saad M. Saleh (Elsevier, 2019)
The preformation probability of alpha cluster in the even-even actinide nuclei was determined using the cluster-formation model. The actinides chosen were with high and low intensity of alpha-decay mode. The results showed well production of preformation probability, which had consistence with other even-even heavy alpha-decay nuclei. Actinides have alpha cluster preformation before the emission as the heavy nuclei. The behavior of the preformation probability indicated new submagic shell at N = 142 and 146 and clearly confirmed those of N = 126 and 152.